Different shape of GaAs quantum structures under various growth conditions - Kim, Jaesu; Jo, Byounggu; Lee, Kwang-Jae; Park, Dongwoo; Lee, Cheul-Ro; Kim, Jin Soo; Jeong, Mun Seok; Byeon, Clare Chisu; Kang, Hoonsoo; Kim, Jong Su; Song, Jin Dong; Choi, Won Jun; et al. (ELSEVIER SCIENCE SA, 2010)
We report the influences of growth parameters on the characteristics of GaAs quantum rings (QRs) and quantum dots (QDs) formed on AlGaAs/GaAs by the droplet epitaxy (DE) method. After forming Ga droplets on the AlGaAs/GaAs surface, varying amounts of arsenic (As) flux were introduced to fabricate the GaAs quantum structures. By decreasing the As flux from 8 x 10(-5) to 3 x 10(-5) Torr, the shape of the GaAs quantum structures was changed from QDs to elongated QRs. With further decreasing As flux, the shape of the elongated QRs became symmetric. The formation characteristics of the GaAs QRs from the QDs with the amount of As flux were discussed in terms of migration behaviors of the gallium (Ga) atoms on the GaAs (001)-c(4 x 4) surface. The effects of the amount of Ga supply and the growth temperature for the deposition of Ga droplets on the formation of the GaAs quantum structures were also considered. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: DROPLET EPITAXY; DOTS